(untitled) (Update Dental College Journal, 2017)
Adequate and safe blood supply has remained a challenge in developing countries like ours. There is a high dependency on family replacement and remunerated blood donors in our environment which carries an attendant increased risk of transfusion transmissible infection. This descriptive type of cross sectional study was conducted at transfusion medicine department of National Institute of Neurosciences & Hospital in Dhaka city during the period January to December 2015 with the aim to assess the awareness about blood donation among donors which includes knowledge and practice of blood donation. A total purposively selected 150 donors were interviewed by using a structured questionnaire which focused on knowledge and practice related variables. The statistical analysis was done by using the SPSS software (Version-21). The associations between the demographic factors were analyzed by using the Chi square test and Fishers Exact test. Among 150 donors, 124 (82.7%) were male and 26 (17.3%) were female donors, the mean age of the donors was 28.4 (± 7.2) years. 78 (52.0%) donors knew about the interval of blood donation and 84 (56.0%) knew about the age limit for the donation, but 86 (57.3%), 71 (47.3%) did not know the required Hb level to donate blood and volume of blood in each donation respectively. More than half (56.0%) had past history of blood donation and 103 (68.6%) of the donors showed positive effects like a feeling of satisfaction after blood donation. There were highly significant association found between blood donation and sex (p value.016). A majority (86.9%) of the donors were willing to be regular donors. The donors showed positive effects like a sense of satisfaction after the donation. Creating an opportunity for blood donation by conducting many blood donation camps may increase the voluntary blood donations. Update Dent. Coll. j: 2016; 6 (2): 21-26